Picture of Hand Washing Behavior with Soap (CTPS) of Students of SDN 029 Botto, Campalagian District - Harum, Habil; Nengsi, Sri (PSPP JOURNALS, 2024)
Washing hands with soap (CTPS) is one of the sanitation actions by cleaning hands and fingers using water and soap so that they are clean. Washing hands with soap is the process of mechanically removing dirt and dust from the skin of both hands using water and soap, washing hands with soap is a simple, easy, and useful way to prevent various diseases that cause death, which can be prevented by washing hands properly, such as diarrhea and ARI which are often the cause of death in children. Behavior is a biological manifestation of individuals in interactive activities with their environment, both in the form of visible and invisible behavior. can be felt to those that cannot be felt. The purpose of the study was to determine the description of hand washing behavior with soap (ctps) in students of SDN 029 Botto Village, Campalagian District. The method used in this study is a qualitative research method by interviewing informants to explore information, informants' attitudes in behaving hand washing with soap (CTPS) in students of SDN 029 Botto, Campalagian District, using 10 informants consisting of fifth and sixth grade students. The conclusion of this study is that students' behavior regarding washing hands with soap is good but not yet optimal and needs to be improved again to achieve a level of health. Therefore, it is necessary to improve the implementation of PHBS, especially washing hands with soap and the completeness of CTPS facilities at SDN 029 Botto school.